Леонид Прозоров. Графика: альбом / Леонид Прозоров - Прозоров Леонид Алексеевич (Удмуртия, 2023)
Экземпляры: аб. (20240220) / Инвентарный номер: 64447 / Цена: / Сис.шифр: 85.143(2Рос.Удм) / Авт.знак: П 79 / ГРНТИ: 18.31 / ББК: 85.143(2Рос.Удм)